1998
DOI: 10.1103/physrevlett.80.4574
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of3dImpurities on the (001) Surface of Iron

Abstract: Motivated by recent STM results for Cr on Fe(001) we present a detailed ab-initio study of the alloying process in the dilute limit for 3d atoms on the Fe(001) surface. The calculations are based on local density functional theory and apply a KKR{Green's function method for impurities on surfaces. For practically all 3d transition metal impurities on Fe(001) we nd a strong tendency for a direct exchange mechanism into the rst surface layer. The early 3d impurities V, Cr and Mn strongly repel each other on neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 12 publications
5
51
1
2
Order By: Relevance
“…These results are in agreement with previous ab initio calculations. 27 In both cases the magnetic ordering is a consequence of the rather long-range exchange coupling between the Mn and Fe atoms. The value of the exchange coupling parameter (J ij ) between the Mn adatom and its four Fe nearest neighbors [Fe1(S)] localized in the surface layer, calculated from the ferromagnetic configuration, is J Mn−Fe1(S) = −2.7 meV.…”
Section: Collinear Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with previous ab initio calculations. 27 In both cases the magnetic ordering is a consequence of the rather long-range exchange coupling between the Mn and Fe atoms. The value of the exchange coupling parameter (J ij ) between the Mn adatom and its four Fe nearest neighbors [Fe1(S)] localized in the surface layer, calculated from the ferromagnetic configuration, is J Mn−Fe1(S) = −2.7 meV.…”
Section: Collinear Structuresmentioning
confidence: 99%
“…6,9,[18][19][20][21][22][23][24][25][26] Nevertheless, only a few studies have been carried out for supported Mn clusters on a bcc Fe(001) surface. 19,27 With the experimental techniques now available, nanowires and nanostructures may be deposited on magnetic and nonmagnetic surfaces in a controlled fashion, and their fundamental magnetic properties can be explored with the use of advanced experimental methods. [28][29][30][31][32][33][34] From the above discussions, it is quite evident that the magnetic interactions at the interface between Mn and Fe have a very rich variety depending on the geometry and local environment.…”
Section: Introductionmentioning
confidence: 99%
“…10,17 Those calculations showed that Co and Ni ''prefer'' ferromagnetic alignment with respect to the substrate, while V and Cr align antiferromagnetically. The case of Mn is critical, since a Mn adatom couples ferromagnetically to Fe moments, while in the first surface layer the antiferromagnetic configuration has a lower energy.…”
Section: Impurities In Fe"001…mentioning
confidence: 99%
“…9 The ground-state properties of single impurities on the Fe͑001͒ surface were recently studied theoretically. 10 For 3d and 4d impurities it was found that impurities from the beginning of the series couple antiferromagnetically to the Fe moments, while impurities from the end of the series couple ferromagnetically. Total-energy calculations showed that for most 3d impurities the adatom position is instable against a direct exchange mechanism, resulting in an integration of the impurities into the first layer, as observed experimentally for Cr impurities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation